Answer:
60 muffins
Step-by-step explanation:
Find out how much ml you need for each ingredient.
20 muffins =
220 ÷ 20 = 11 (milk)
250 ÷ 20 = 12.5 (castel sugar)
400 ÷ 20 = 20 (flour)
Find out the greatest number of muffins Jack can make.
1 litre = 1000 ml
1000 ÷ 11 = 90.90 (recurring decimal) (milk)
750 ÷ 12.5 = 60 (castel sugar)
1500 ÷ 20 = 75 (flour)
Find the smallest answer out of the 3 questions.
Answer:
The measure of arc SQ is 95° ⇒ (1)
Step-by-step explanation:
- The measure of any circle is 360°
- The measure of the subtended arc to an inscribed angle is twice the measure of this angle
In the given circle
∵ S lies on the circumference of the circle
∴ ∠QSR is an inscribed angle
∵ ∠QSR is subtended by arc QR
→ By using the 2nd rule above
∴ m arc QR = 2 × m∠QSR
∵ m∠QSR = 95°
∴ m arc QR = 2 × 95
∴ m arc QR = 190°
→ By using the 1st rule above
∵ m of the circle = m arc QR + m arc SQ + m arc SR
∵ m arc SR = 75° and m arc QR = 190°
→ Substitute them in the equation above
∴ 360 = 190 + m arc SQ + 75
→ Add the like term in the right side
∴ 360 = 265 + m arc QS
→ Subtract 265 from both sides
∵ 360 - 265 = 265 - 265 + m arc SQ
∴ 95° = m arc SQ
∴ The measure of arc SQ is 95°
The solution can be anything bigger than 13/6.
For example: 3, 4, 5, 6...ect
Answer:
-139
Step-by-step explanation:
Evaluate 1/4 (4 x^3 - 2 y - 2 z^3) y^2 - 16 x^2 where x = 2, y = -5 and z = 3:
(4 x^3 - 2 y - 2 z^3)/4 y^2 - 16 x^2 = (4×2^3 - -5×2 - 2×3^3)/4×(-5)^2 - 16×2^2
(4×2^3 - 2 (-5) - 2×3^3)/4×(-5)^2 = ((4×2^3 - 2 (-5) - 2×3^3) (-5)^2)/4:
((4×2^3 - 2 (-5) - 2×3^3) (-5)^2)/4 - 16×2^2
(-5)^2 = 25:
((4×2^3 - 2 (-5) - 2×3^3) 25)/4 - 16×2^2
2^3 = 2×2^2:
((4×2×2^2 - 2 (-5) - 2×3^3) 25)/4 - 16×2^2
2^2 = 4:
((4×2×4 - 2 (-5) - 2×3^3) 25)/4 - 16×2^2
2×4 = 8:
((4×8 - 2 (-5) - 2×3^3) 25)/4 - 16×2^2
3^3 = 3×3^2:
((4×8 - 2 (-5) - 23×3^2) 25)/4 - 16×2^2
3^2 = 9:
((4×8 - 2 (-5) - 2×3×9) 25)/4 - 16×2^2
3×9 = 27:
((4×8 - 2 (-5) - 227) 25)/4 - 16×2^2
4×8 = 32:
((32 - 2 (-5) - 2×27) 25)/4 - 16×2^2
-2 (-5) = 10:
((32 + 10 - 2×27) 25)/4 - 16×2^2
-2×27 = -54:
((32 + 10 + -54) 25)/4 - 16×2^2
| 3 | 2
+ | 1 | 0
| 4 | 2:
(42 - 54 25)/4 - 16×2^2
42 - 54 = -(54 - 42):
(-(54 - 42) 25)/4 - 16×2^2
| 5 | 4
- | 4 | 2
| 1 | 2:
(-12×25)/4 - 16×2^2
(-12)/4 = (4 (-3))/4 = -3:
-3×25 - 16×2^2
2^2 = 4:
-3×25 - 164
-3×25 = -75:
-75 - 16×4
-16×4 = -64:
-64 - 75
-75 - 64 = -(75 + 64):
-(75 + 64)
| 7 | 5
+ | 6 | 4
1 | 3 | 9:
Answer: -139
Answer:
7
Step-by-step explanation: